2005
DOI: 10.1071/rd04060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypobaric hypoxia on lamb intrauterine growth: comparison between high- and low-altitude native ewes

Abstract: The present studies assessed the effect of hypobaric hypoxia on fetal lamb growth in high-altitude (HA) and low-altitude (LA) native ewes. Growth patterns of fetal biparietal diameter (BPD), abdominal diameter (AD) and thorax height (TH) were described by consecutive ultrasound measurements throughout the entire pregnancy. Three groups of animals were used: (1) pregnant LA ewes kept at LA (control; 'LL' group); (2) pregnant LA ewes moved to HA immediately after confirmation of pregnancy ('LH' group); and (3) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…In our study, both groups of lambs received the same nutrition, so the changes observed in pulmonary arterial pressure and growth restriction appear to be independent of nutrition. Accordingly, the effects on fetal growth restriction and mortality of developmental hypoxia at high altitude have been shown to be independent of the maternal nutritional status and of highland hypobaria in other species, since fetal growth restriction persists in ewes undergoing pregnancy at high altitude with food intake values similar to those as sea level pregnancies (23, 39). These effects have also been shown in the chick embryo, where incubation at high altitude of sea level eggs with oxygen supplementation completely prevented the high altitude-induced fetal growth restriction and mortality (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, both groups of lambs received the same nutrition, so the changes observed in pulmonary arterial pressure and growth restriction appear to be independent of nutrition. Accordingly, the effects on fetal growth restriction and mortality of developmental hypoxia at high altitude have been shown to be independent of the maternal nutritional status and of highland hypobaria in other species, since fetal growth restriction persists in ewes undergoing pregnancy at high altitude with food intake values similar to those as sea level pregnancies (23, 39). These effects have also been shown in the chick embryo, where incubation at high altitude of sea level eggs with oxygen supplementation completely prevented the high altitude-induced fetal growth restriction and mortality (17).…”
Section: Discussionmentioning
confidence: 99%
“…The diminished production of CO by the pulmonary circulation determined in this study may play a putative role in the maintenance of persistent pulmonary hypertension of the newborn at sea level. In addition, chronic developmental hypoxia is known to result in lung hypoplasia and immaturity, pulmonary edema, and altered endothelial function (2, 20, 39, 46). Alterations in the synthesis and function of vasoconstrictors such as ET-1, as reported in this paper, thromboxane, IGF, serotonin, and leukotriene C 4 /D 4 have also been implicated in the pulmonary hypertensive phenotype during chronic hypoxia (29, 45).…”
Section: Discussionmentioning
confidence: 99%
“…; Penninga & Longo, ; Parraguez et al . ). Taken together, these observations suggest that there are adaptations in materno‐fetal resource allocation during chronic hypoxia that help to maintain fetal growth, although the mechanisms operating in vivo remain unknown.…”
Section: Introductionmentioning
confidence: 97%
“…) and in domestic animal species (mainly sheep) introduced to high plateaus (Lanino ; De Carolis ; Parraguez et al. , ). The low reproductive efficiency is even more marked in newcomers to high altitude, by acute exposition to hypoxia, both humans (Moore et al.…”
Section: Introductionmentioning
confidence: 99%
“…) and sheep (Parraguez et al. , ). These facts are of main importance, firstly, for human medicine; approximately 140 millions of people inhabit at altitudes above 2500 m above sea level (m.a.s.l.…”
Section: Introductionmentioning
confidence: 99%